STRUKTUR NARATIF LEGENDA GUNUNG MUTIS DI KABUPATEN TIMOR TENGAH SELATAN - Fridus Eldijen Natonis; Labu Djuli; Semuel H. Nitbani (Jurnal Lazuardi, 2026)
This study analyzes the narrative structure of the legend of Mount Mutis in South Central Timor Regency. The purpose of this study is to describe the narrative structure of the legend of Mount Mutis in South Central Timor Regency. The theory used is Seymour Chatman's narrative structure theory. The method used in this study is descriptive qualitative. Data collection techniques used are interview techniques, recording techniques, note-taking techniques, determining kernels and satellites, tabulating data or entering all data into coding cards, and determining textual sequences, logical sequences, chronological sequences, characters and settings. Data analysis techniques used in this study are, translating data, sorting data, determining characters (figures and characterizations), determining settings and concluding data based on data analysis. Data was identified using Seymour Chatman's Narrative Structure theory, which included textual sequence, logical sequence, chronological sequence, characters, and setting. The analyzed data presentation technique will be described verbally, using words rather than numbers. The results of the study indicate that the textual sequence of the story above is described sequentially, starting with the initial development of the story or major premise and continuing to the minor premise. The logical sequence has five kernels and is explained coherently. The chronological sequence uses a forward flow, beginning with the beginning, middle, and end of the legend of Mount Mutis. The conclusion describes the number of textual sequences, logical sequences, chronological sequences, characters, and settings based on the research findings.